Benefit and cost analysis of Kampung Melayu as a religion tourism - Al Muqsit, Faruq; Prihestiwi, Rosa Calista; Yosliansyah, Mohamad Rizalby; Pranata, Muhammad Deriel Ari; Pramesti, Arinda Faradila (Proceeding International Conference on Accounting and Finance, 2024)
The government is committed to improving regional economic growth by stimulating local economic development, one facet being the advancement of religious tourism. The story of religious tourism shows significant potential, evidenced by numerous provinces instituting religious tourism programs, resulting in a steady increase in tourist visitation. Kampung Melayu is one of the villages in Semarang City that has the potential for religious tourism. The purpose of writing this article is to formulate potential sources of financing and to analyze the cost benefits arising from the development of the Kampung Melayu area based on the perspective of two stakeholders, namely the government and the project manager. This stakeholder difference brings a unique perspective to the development of Malay villages as religious tourism. The method used is a qualitative descriptive analysis method that looks at the condition of the study area and calculates the cost and benefit analysis to see the economic and financial feasibility. This study has three parts: identification of area development, potential economic activities, and financing of area development. The results of the analysis show that the financial and economic feasibility of the Kampung Melayu Semarang development project has proven feasible to implement. The NPV value is positive (+), and the BCR is more than 1, indicating a potential for financial gain more significant than the costs incurred. In addition, this project also provides substantial economic benefits, reflecting its success in achieving financial goals and positively impacting the economy.